Highly thermally conductive phase change composites for thermal energy storage featuring shape memory. (February 2020) - Luo, Fubin; Yan, PinPing; Qian, Qingrong; Li, Hongzhou; Huang, Baoquan; Chen, Qinghua; Wu, Kun; Lu, Mangeng
Abstract: Highly thermally conductive form-stable phase change materials (PCMs) possessing shape memory are designed based on covalent-noncovalent interpenetrating polymer network and boron nitride. The matrix network relies on the composition of two functional species, cured mesogenic epoxy (EO) and polyethylene glycol (PEG). It is demonstrated that the covalent network of EO can trap PEG by forming hydrogen bond with PEG chains. On the basis of EO/PEG networks, by incorporating boron nitride, the thermally conductivity of the PCMs can reach to 2.962 W m −1 K −1 . The prepared composites show satisfied thermal energy storage capability and good shape stability when undergo long time heating at 80 °C. In addition, the prepared composite exhibits excellent shape memory function. Diverse functions of the PCMs might produce new applications in thermal energy storage or thermal management fields.